Effectiveness of indirect free kicks in elite soccer - Casal, C. A.; Maneiro, R.; Ardá, T.; Losada, J. L; Rial, A. (International Journal of Performance Analysis in Sport, 2014)
The aims of this study were to determine the effectiveness of indirect free kicks, identify variables associated with a successful outcome, and propose a model for taking free kicks with an increased probability of success. The analysis focused on 783 free kicks taken in 124 matches at the 2010 FIFA World Cup, the final stages of the UEFA Champions League in 2010/11, and the 2010 UEFA Euro-pean Championships. The following variables were studied by univariate, biva-riate, and multivariate analyses: time of the match when the indirect free kick was taken, position and laterally of the kick, number of attackers, number of defenders, interaction context, delivery of ball, path of ball, type of marking, number of intervening attackers, area to which the ball was passed, shooting area, offensive organization, type of shot, and match status. The results show that almost 36 indirect free kicks are needed to score a goal, but that 64% of goals from indirect free kicks have a decisive influence on game outcome. Goals were more common when the attack was organized dynamically and three or four players touched the ball before a shot was taken. These findings could help coaches to improve free-kick performance.